The comparative efficacy of kinesio taping and local injection therapy in patients with subacromial impingement syndrome - Hamit Göksu; Figen Tuncay; Pınar Borman (Acta Orthopaedica et Traumatologica Turcica, 2016)
Objective: The aim of this study was to compare the therapeutic effects of kinesio taping (KT) and local subacromial injection in patients with subacromial impingement, syndrome (SIS) with regard to pain, range of motion (ROM) and disability. Methods: Sixty-one patients (48 females and 13 males; mean age: 43.04 ± 6.31, years) with SIS were enrolled into the study. The patients were randomized into two treatment groups receiving either a single corticosteroid and local anesthetic (LA) injection, or kinesio taping performed three times by intervals of 3 day. Visual analog scale (VAS) was used to assess pain intensity, range of motion (ROM) degrees of, shoulder were recorded and Shoulder Pain and Disability Index (SPADI) was, performed to evaluate functional disability, before treatment, at the first and fourth, weeks after therapies. A exercise program was prescribed for both groups including pendulum, active range of motion (ROM) and strengthening exercises. Results: Pain, functional outcome measures were determined to have improved significantly in both groups at the end of therapies at first and fourth weeks (p < 0.05), but these improvements were more significant in the injection group than in kinesio taping group (p < 0.05). The improvements in pain at rest, shoulder abduction degrees, and SPADI scores at first and fourth weeks were statistically higher in injection group than in kinesio taping group. Conclusion: Although the improvement in pain intensity at rest, ROM and disability were better with local injection, KT may be an alternative noninvasive method to local subacromial injection for patients suffering from subacromial impingement syndrome. Level of Evidence: Level I, Therapeutic study. Keywords: Subacromial impingement syndrome, Steroid injection, Kinesio taping, Subacromial injection